Lithium Niobate – Enhanced Photoacoustic Spectroscopy - Aldo F.P. Cantatore; Giansergio Menduni; Andrea Zifarelli; Pietro Patimisco; Miguel Gonzalez; Huseyin R. Seren; Vincenzo Spagnolo; Angelo Sampaolo (Photoacoustics, 2024)
In this work, we report on the novel employment of lithium niobate tuning forks as acoustic transducers in photoacoustic spectroscopy for gas sensing. The lithium niobate tuning fork (LiNTF) exhibits a fundamental resonance frequency of 39196.6 Hz and a quality factor Q = 5900 at atmospheric pressure. The possibility to operate the LiNTF as a photoacoustic wave detector was demonstrated targeting a water vapor absorption line falling at 7181.14 cm−1 (1.39 µm). A noise equivalent concentration of 2 ppm was reached with a signal integration time of 20 s. These preliminary results open the path towards integrated photonic devices for gas sensing with LiNTF-based detectors on lithium niobate platforms.